PENERAPAN PERSONNEL CONTROL DAN CULTURAL CONTROLTERHADAP PENINGKATAN MOTIVASI KERJA KARYAWAN PADA CV SEJATI MALANG - Selina Fransisca; Ria Sandra Alimbudiono (Perpustakaan Universitas Surabaya, 2018)
Management control system has an important role in a business entity in order to achieve the vision and mission of the company. In the development of business entity certainly has the human resources as a driver with a variety of individuals who have different backgrounds and goals. Therefore, the business entity requires a management control system. Management control system there are four kinds of action control, result control, personnel control and cultural control.This thesis contains research on the implementation of personnel control and cultural control in a business entity of pharmacy with research object employees of the financial division, sales division and warehouse division. In this thesis disclosed about the motivation problems that cause the decrease of employee’s motivation from CV Sejati. To be able to do a good job so as to achieve maximum performance, employees must be motivated both internally and externally through personal and cultural control.